Blast resistance of CC-NB-LRR protein Pb1 is mediated by WRKY45 through protein–protein interaction - Inoue, Haruhiko (National Academy of Sciences, 2013)
Panicle blast 1 (Pb1) is a panicle blast resistance gene derived from the indica rice cultivar “Modan.” Pb1 encodes a coiled-coil–nucleotide-binding site–leucine-rich repeat (CC-NB-LRR) protein and confers durable, broad-spectrum resistance to Magnaporthe oryzae races. Here, we investigated the molecular mechanisms underlying Pb1-mediated blast resistance. The Pb1 protein interacted with WRKY45, a transcription factor involved in induced resistance via the salicylic acid signaling pathway that is regulated by the ubiquitin proteasome system. Pb1-mediated panicle blast resistance was largely compromised when WRKY45 was knocked down in a Pb1-containing rice cultivar. Leaf-blast resistance by Pb1 overexpression (Pb1-ox) was also compromised in WRKY45 knockdown/Pb1-ox rice. Blast infection induced higher accumulation of WRKY45 in Pb1-ox than in control Nipponbare rice. Overexpression of Pb1-Quad, a coiled-coil domain mutant that had weak interaction with WRKY45, resulted in significantly weaker blast resistance than that of wild-type Pb1. Overexpression of Pb1 with a nuclear export sequence failed to confer blast resistance to rice. These results suggest that the blast resistance of Pb1 depends on its interaction with WRKY45 in the nucleus. In a transient system using rice protoplasts, coexpression of Pb1 enhanced WRKY45 accumulation and increased WRKY45-dependent transactivation activity, suggesting that protection of WRKY45 from ubiquitin proteasome system degradation is possibly involved in Pb1-dependent blast resistance.